Deep Vein Thrombosis in Primary Care: A Narrative Review with a Clinical Case Scenario - Sadaf Noureen; Shatha Taha (SAS Journal of Medicine, 2026)
Deep vein thrombosis (DVT) is a common and potentially life-threatening manifestation of venous thromboembolism that frequently presents first in primary care. Prompt recognition is challenging because symptoms such as unilateral leg pain, swelling, warmth, and tenderness are nonspecific and may resemble several musculoskeletal, inflammatory, and vascular conditions. This review discusses the epidemiology, pathophysiology, risk factors, clinical presentation, diagnosis, treatment, and long-term management of DVT from a primary-care perspective. A clinical case illustrates the application of the two-level Wells score, D-dimer testing, and proximal leg-vein ultrasonography in accordance with current guidance. When indicated imaging cannot be completed promptly, interim therapeutic anticoagulation is essential to reduce the risk of pulmonary embolism and other complications. Direct oral anticoagulants, particularly apixaban and rivaroxaban, are suitable first-line treatments for most adults, although renal function, bleeding risk, pregnancy, malignancy, drug interactions, and patient preference must be considered. Anticoagulation should generally continue for at least three months, with further treatment individualised according to whether the event was provoked or unprovoked and the balance between recurrence and bleeding risks. Primary care also has a central role in monitoring adherence, recognising complications, providing patient education, and reviewing the need for extended anticoagulation. A structured, probability-based diagnostic approach, timely referral, appropriate interim treatment, and planned long-term follow-up can substantially improve outcomes for patients with suspected or confirmed DVT.